A novel electrical approach to protect PV modules under various partial shading situations. (15th November 2019) - Hanifi, Hamed; Pander, Matthias; Jaeckel, Bengt; Schneider, Jens; Bakhtiari, Afshin; Maier, Waldemar
Highlights: Development and introduction of a new high tolerance PV module design. Comparison of novel design with standard modules. Electrical and mechanical characterization and tests. Development of new test device for electrical stressing of bypass diodes. Abstract: Partial shading is one of the challenges of PV modules. Even very small partial shading can lead to a considerable power loss in PV modules. Reoccurring partial shading in combination of the presence of local defects increases the risk of hot-spots in PV modules. Hot-spots could lead to failure (e.g. browning, bubble formation and breakdown of insulation system) and therefore to a decrease of service life of the PV modules. In typical crystalline silicon PV modules, every module string is protected by a bypass diode. The bypass diodes protect the shaded solar cell from high reverse current before its breakdown voltage is reached. However, it bypasses also the other unshaded solar cells of the string and therefor typically a third of the module output power is lost. In this work, we analyze and compare a standard 60-cell c-Si PV module with 3 bypass diodes with a hot-spot-free module in which every solar cell is protected with an individual bypass diode. Different partial shading conditions are applied to both modules and the results show that under different shading scenarios, hot-spot-free module show 32% and 80% higher power production compared to the standard module. To investigate the reliability of the bypass diode under shading conditions, we have developed a novel testing setup which switches the bias every 60 s and monitors the temperature by IR camera. The results show that the module is reliable enough to meet 25 years lifetime.